2003
DOI: 10.1016/s0194-5998(03)00525-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sensitization to inhalative allergens on adenotonsillar disease

Abstract: Both atopic and nonatopic children with adenotonsillar disease improve health after adenoidectomy or adenotonsillectomy. In our opinion, routine allergy tests before adenotonsillectomy or adenoidectomy are not justified. Only if allergy is suspected due to clinical findings or family history should an allergy test be carried out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…He also examines the influence of atopy on the adenoid hypertrophy and suggests that allergic rhinitis is an important risk factor for adenoid hypertrophy in children and in other study they examined the incidence of adenoid hypertrophy in allergic children and concluded that the risk of adenoid hypertrophy in allergic children hypersensitive to dust mites is greater only in them with allergic rhinitis [18,19]. Hofman et al studied the influence of IgE-mediated sensitization on adenotonsillar disease in children and showed 22.9% of adenotonsillecttomid children had positive Rast results to inhalative allergens [20].…”
Section: Discussionmentioning
confidence: 99%
“…He also examines the influence of atopy on the adenoid hypertrophy and suggests that allergic rhinitis is an important risk factor for adenoid hypertrophy in children and in other study they examined the incidence of adenoid hypertrophy in allergic children and concluded that the risk of adenoid hypertrophy in allergic children hypersensitive to dust mites is greater only in them with allergic rhinitis [18,19]. Hofman et al studied the influence of IgE-mediated sensitization on adenotonsillar disease in children and showed 22.9% of adenotonsillecttomid children had positive Rast results to inhalative allergens [20].…”
Section: Discussionmentioning
confidence: 99%
“…Forty-two children (73.68%) had polysensitization and 15 children (26.32%) had single sensitization. Congruent with previous literature, polysensitization was found to be more common in children with ATH [3]. Because of the high polysensitization ratio and small size of our study group, we did not perform statistical analyses to determine which allergen is more eosinophilic.…”
Section: Discussionmentioning
confidence: 73%
“…Allergy is one of the most common inflammatory processes for the upper respiratory tract [1]. Despite the fact that the prevalence of adenotonsillar disease is reported as 21.2% and 22.9% in some studies [2,3] in children with allergic rhinitis (AR), Griffin et al [4] reported that the prevalence of AR is similar to age-matched controls.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of sensitization to inhalant allergens apparently alters the immunology of adenoid tissue. Children with adenotonsillar disease have improved general health and nasal symptoms after adenoidectomy, regardless of whether they are atopic or nonatopic 15 . Saito et al 4 found that asthma symptoms improved in 88% of asthmatic children, and 60% of the children were able to eliminate the use of all medications after adenoidectomy or adenotonsillectomy.…”
Section: Discussionmentioning
confidence: 99%